Relationship between free and total malondialdehyde, a well-established marker of oxidative stress, in various types of human biospecimens - Cui, X. X.; Gong, J. C.; Han, H. L.; He, L. C.; Teng, Y. B.; Tetley, T.; Sinharay, R.; Chung, K. F.; Islam, T.; Gilliland, F.; Grady, S.; Garshick, E.; et al. (Journal of Thoracic Disease, 2018)
Background: Oxidative stress is involved in thoracic diseases and health responses to air pollution. Malondialdehyde (MDA) is a well-established marker of oxidative stress, but it may be present in unconjugated and conjugated forms. To our knowledge, no studies have conducted a systemic evaluation of both free MDA (unconjugated MDA) and total MDA (the sum of both unconjugated and conjugated MDA) across various types of human biospecimens.Methods: Free MDA and total MDA were simultaneously measured in a range of human biospecimens, including nasal fluid (N=158), saliva (N=158), exhaled breath condensate (N=40), serum (N=232), and urine (N=429). All samples were analyzed using an HPLC-fluorescence method with high sensitivity and specificity. Due to the right skewed distribution of free MDA and total MDA, we performed natural-log transformation before subsequent statistical analyses. The relationship between the natural log of free and total MDA was evaluated by R-2 of simple linear regression. T test was used for comparisons of means between two groups. One-way analysis of variance was used in combination with Tukey's test to compare the natural log of the ratio of free MDA to total MDA across various types of biospecimens.Results: For exhaled breath condensate, serum, urine, nasal fluid and saliva samples, the R-2 between free and total MDA were 0.61, 0.22, 0.59, 0.47 and 0.06, respectively; the medians of the free MDA to total MDA ratio were 48.1%, 17.4%, 9.8%, 5.1% and 3.0%, respectively; the free MDA to total MDA ratio in EBC > serum > urine > nasal fluid > saliva (P < 0.001 for pairwise comparisons).Conclusions: For exhaled breath condensate and urine samples, using either free or total MDA can provide information regarding the level of oxidative stress; however, that is not the case for serum, nasal fluid, and saliva given the low correlations between free and total MDA.
Keywords: air-pollution; biological markers; biomarkers; disease; exhaled breath condensate; healthy; lipid-peroxidation; malonaldehyde; malondialdehyde (mda); nasal fluid; nasal secretions; Oxidative Stress; saliva; serum; total plasma malondialdehyde; urine